Sustainable tourism as a driving force in regional development of remote regions in Siberia: An integrated operational framework - Vitálišová, Katarína; Borseková, Kamila; Blam, Inna (Quaestiones Geographicae, 2021)
Regional development based on sustainable tourism is one of the options of developing remote regions, which are usually disadvantaged due to their distance, but can have a certain competitive advantage based on their remoteness. The present paper offers in-depth analysis of the tourism potential in selected remote regions of Russia, the Altai Mountains and Lake Baikal with the aim to explore the specific features of their sustainable tourism development and to propose an integrated operational framework for sustainable tourism and regional development usable for similar regions across the world. The proposed integrated operational framework helps to achieve a tricky balance between economic resurrection of remote areas and environment conservation, which is possible only with the proper co-integration of tourists with the community, and local economic development with the environment. It presents a set of drivers and their mutual relations to achieve the successful sustainable tourism development in remote regions in Russia and across the world. The present research results contribute to a knowledge bank that could serve as a useful guide for academics and policymakers involved with sustainable development, geography or environmentally sensi- tive tourism